2020
DOI: 10.1039/d0cc02498h
|View full text |Cite
|
Sign up to set email alerts
|

Profiling structural diversity and activity of 2-alkyl-4(1H)-quinolone N-oxides of Pseudomonas and Burkholderia

Abstract: Here, we report the synthesis of all major 2-alkyl-4(1H)-quinolone N-oxide classes of Pseudomonas and Burkholderia, quantification of their native production levels and their antibiotic activities against competing Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…These nodes correspond to C9 HHQ (4-heptyl-4( 1H )-quinolone) congeners, the C9 HHQdb, and the C7 and C9 HQNOs (2-heptyl-4-hydroxyquinoline-N-oxide) and their double-bonded congeners (see Figure 7 C, Figures S52 and S53 ). These findings are consistent with the literature where more than 50 diverse HAQs have been identified, C7 and C9 congeners being the most abundant [ 66 , 67 ]. Comparison of this cluster with that recorded with incubation with 2 or 4, showed that no HAQs appeared to be significant except for the C4 HHQ and C6 HHQdb.…”
Section: Resultssupporting
confidence: 93%
“…These nodes correspond to C9 HHQ (4-heptyl-4( 1H )-quinolone) congeners, the C9 HHQdb, and the C7 and C9 HQNOs (2-heptyl-4-hydroxyquinoline-N-oxide) and their double-bonded congeners (see Figure 7 C, Figures S52 and S53 ). These findings are consistent with the literature where more than 50 diverse HAQs have been identified, C7 and C9 congeners being the most abundant [ 66 , 67 ]. Comparison of this cluster with that recorded with incubation with 2 or 4, showed that no HAQs appeared to be significant except for the C4 HHQ and C6 HHQdb.…”
Section: Resultssupporting
confidence: 93%
“…To date, bacterial quinolone N-oxides have only been isolated from members of the Pseudomonas genus, with only one exception: a C-3 methylated N-oxide (CN9Δ2) produced by an Arthrobacter species [29]. However, a range of unsaturated derivatives have been detected by MS in Burkholderia strains [30].…”
Section: Structural Diversity and Distributionmentioning
confidence: 99%
“…A 2020 report described the LC-MS analysis of quinolone derivatives in three microbial strains by multiple reaction monitoring (MRM). With the aid of synthetic standards the authors were able to confirm the location of the double bonds in the unsaturated derivatives: all quinolones with an unsaturated side chain produced by the Burkholderia strains possessed a double bond at the 2 -position, while those produced by Pseudomonas species had double bonds at either the 1 or 2 positions [30].…”
Section: Metabolic Profilingmentioning
confidence: 99%
“…6 Homologous biosynthetic gene clusters also exist in species of the genus Burkholderia 7 producing unique methylated quinolone congeners. 8,9 These 3methyl-2-alkylquinolones (MAQs) ‡ are non-classical quorum sensing signals in Burkholderia and have been implicated in regulating homoserine lactone quorum signalling. 10 The genus Burkholderia comprises important pathogens such as B. pseudomallei, the causative agent of melioidosis 11 and species of the B. cepacia complex including B. ambifaria and B. multivorans which are responsible for severe infections in cystic brosis (CF) patients.…”
mentioning
confidence: 99%
“…2a). We synthesized several a-chloroketones (1-4) using the Houben-Hoesch reaction (Scheme 1) and combined them with commercially available compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) to generate a small library (Fig. 2b).…”
mentioning
confidence: 99%